Life Skills Paradigm Based Intervention on Decision Making Skill for Healthy Eating Habits of Adolescent Girl Students - Meena,; Sood, Ridhi (INDIAN EDUCATIONAL REVIEW, 2015)
The present study employed the pre-test, post-test control group design on ninety adolescent girl students to examine the effect of Life Skills Paradigm (intervention) on their decision making skill for healthy eating habits. The major findings of the study indicated: (i) significant differences in the mean scores of decision making skill in Life Skills Paradigm interventional and non-interventional group, (ii) significant difference in pre-post mean scores of decision making skill in life skills paradigm interventional group, (iii) no significant difference in pre-post mean scores of decision making skill in non-interventional group, and (iv) significant effect of life skills paradigm based intervention on decision making skill by taking pre-decision making skill scores as covariate.